A Novel Compact Wideband Bandpass Filter With High Upper Stopband Rejection - Qijun Lu; Jiawei Sun; Hao Zhang; Tao Zhang; Zhangming Zhu (IEEE Journal of Microwaves)
This paper presents a novel compact wideband quadruple-mode bandpass filter (BPF) with four resonant modes and five transmission zeros (TZs). Two T-shaped stepped impedance stub loaded resonators are coupled in parallel to the input and output feed lines to form the entire BPF. To provide a wideband and outstanding rejection in upper stopband, the two TZs are introduced by the stepped impedance stub as well as the designed coupling capacitor, and the two inherent TZs produced by the coupling between the resonators and feed lines are used and carefully tuned. The proposed BPF is fabricated in 65 nm CMOS technology with a core area of 0.072 mm2 (7.1×10-3 λ02). The measurement results show that the 3-dB bandwidth is 24.2 GHz at the center frequency of 94 GHz as well as the minimum insertion loss is 4.6 dB. Meanwhile, the stopband extends to 170 GHz with a stopband rejection above 25 dB.